2013
DOI: 10.1055/s-0032-1328408
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss der Hornhautdicke bei Keratokonus auf die Messung des Augeninnendrucks mit 4 verschiedenen Messverfahren

Abstract: IOPen seemed to be affected by CCT. IOP readings by iCare, GAT and DCT were found to be independent of CCT in keratoconic corneas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…We found that the mean IOP obtained by ICare was significantly lower than those by GAT and Tono-Pen; this is in accordance with results of previous studies [2729]. The difference was approximately 2 mmHg, and so, the statistically significant differences found between GAT and ICare were not considered clinically relevant [27]. We consider the change in corneal rigidity after MyoRing implantation is a possible reason; however, the ICare tonometer was found to be lower.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the mean IOP obtained by ICare was significantly lower than those by GAT and Tono-Pen; this is in accordance with results of previous studies [2729]. The difference was approximately 2 mmHg, and so, the statistically significant differences found between GAT and ICare were not considered clinically relevant [27]. We consider the change in corneal rigidity after MyoRing implantation is a possible reason; however, the ICare tonometer was found to be lower.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, there was no significant correlation between CCT and the mean difference in IOP measurement by different methods. This was the case in the study by Klamann et al, in which they evaluated the effect of CCT of keratoconic corneas on IOP measurements as measured by four different techniques, and they found that ICare and GAT were found to be independent of CCT in keratoconic corneas [27]. This similarity between our results and theirs may be because both studies investigated keratoconus cases.…”
Section: Discussionsupporting
confidence: 86%
“…Conversely to RT, there are many studies investigating DCT measurements in keratoconic corneas. These studies are summarized in Table 4 19, 20, 21, 22, 23, 24, 25, 26. DCT measurements about 4 mm Hg high than GAT measurements in keratoconic corneas shown in Table 4.…”
Section: Discussionmentioning
confidence: 95%